BUNGA BANK: ANTARA PARADIGMA TEKSTUAL DAN KONTEKSTUAL - Muhammad Syarif Hasyim (Hunafa: Jurnal Studia Islamika, 2008)
Bank interest is an interesting topic to discuss from classical era to modern era. In classical era,  interest   has been decided as ribâ., the law status of which   is harâm (forbidden) because of an addition (ziyâdah). Based on this, bank interest is also categorized as ribâ. Nevertheless, some say that the forbiddance of ribâ is because of  an exploitation to  the clients, based on which bank interest is not ribâ. It is based on these two opinions that a controversy  on bank interest emerges. The controversy emerges since the first group interprets the verses on ribâ textually while the second group interprets the verses contextually.Kata Kunci: bunga bank, paradigma tekstual, paradigma  kontekstual